Calidad de servicio percibida y el precio como factores que determinan la satisfacción del cliente en supermercados - Barrera Escobar, Katherine Juvitza (2021)
Currently, the retail sector considers of vital importance the gap that is established between the expectations and perceptions of customers within their shopping experience, which are influenced by various factors, both internal and external, resulting in the rating obtained, by means of the models of the evaluation of the quality of service and, consequently, in the satisfaction generated in the client. The study seeks to analyze and expand the measurement and conceptualization of customer satisfaction in the retail sector, through the quality of service in various supermarkets. The review of service quality literature and the results of qualitative and quantitative studies, carried out by various authors, such as Parasuraman, Zeithaml, Berry, Grönroos, among others, warn that the quality of service in the retail sector in specifically in supermarkets is seen influenced by various dimensions, mainly: tangibility, reliability, responsiveness, security and empathy, as well as other factors. We consider that this research contributes to economic and business sciences in a relevant way, since in a context in which products are not the differential, the quality of service and the satisfaction that is obtained as a consequence, it must overcome the gap of the expectations. This thesis focuses on discovering which are the dimensions that most influence it.